Embracing Technology Get Tech-Savvy by Learning About Your Computer, Smartphone, Internet, and Social Media Applications (English Edition) - R Grover, Maniik; R Grover, Maniik (BPB Publications, 2021)
Your All-in-One Guide to the Digital WorldKey Features? Includes basic concepts about computer hardware and software, device connections, and the Internet.? Solutions on how to get the most out of emails, office suites, photos, videos, and maps.? Insights on social media, e-commerce, digital payments, and online booking.DescriptionTechnology touches our lives in many different ways. In this book, we will explore the common uses of technology in the world around you, demystify the concepts, and explain its usage.The book begins by making you comfortable with your Windows PC and Android Smartphone/Tablet. It discusses the Internet and common device connections. It also delves into popular productivity applications like emails, documents, spreadsheets, presentations, maps, photos, music, and videos. Usage of free apps from Google is demonstrated. The book also talks about social media and online tools which allow you to connect and communicate with people on the Internet, with examples from Facebook, Twitter, Instagram, and WhatsApp. The different facets of e-commerce are discussed as well, namely, payments, online shopping, tracking, reviews, and online travel booking, along with examples from popular shopping and travel websites. It explores newer trends like cloud computing, media players, and voice assistants. Security and privacy best practices are also covered for each topic.This book is an attempt to break down the barriers that stand between you and the digital world and enable you to embrace technology. By the end of this book, you$1 (Bll find yourself more tech-savvy than you were when you started.What you will learn? Day-to-day tasks on your Windows PC, Android Smartphone, and the Internet.? Usage of popular Google services, including Gmail, docs suite, and YouTube.? Usage of Facebook, Twitter, Instagram, Hangouts, and WhatsApp.? Learn how to shop, pay and book flights, hotels, buses, and trains online.? Learn about Media Players and usage of Google Assistant.Who this book is forThis book is for students, parents, kids, senior citizens, housewives, and any person who wants to get acquainted with the essential skills for the digital era and wants to become comfortable with technology, smart devices, and internet applications. To get the best out of this book, you must have either a Windows 10 PC or an Android Smartphone/Tablet, and stable Internet access.Table of ContentsPreface1. Your Smartphone/Tablet2. Your Computer/Laptop3. The Internet4. Connections5. E-mail6. Photos7. Music and Videos8. Productivity Apps9. Maps10. Social Media11. Online Communication12. WhatsApp13. Money and Payments14. Managing your Privacy15. Reviews16. E-commerce17. Booking Travel Online18. Beyond your PC and SmartphoneSumming it upAbout the Authors Maniik R Grover is a Technology Entrepreneur from New Delhi with 20 years of experience in Information Technology (Software). A Telecommunication engineer by education, he has previously worked with Expedia, Yahoo!, Fidelity Investments amongst other software MNCs and startups. Over the last two decades, he has worked on a wide variety of software products for the Internet in the domains of Travel E-commerce, Fraud Prevention, Digital Marketing, VoIP, and Equity Trading.Maniik cares for the cause of Digital Literacy and Digital Inclusion and this book is an initiative towards supporting that cause. Apart from technology, he$1 (Bs enthusiastic about Stock Trading, Perfumery, and singing Karaoke. This is his first book.LinkedIn Profile: https://www.linkedin.com/in/manikgrover/Blog Link: http://manikgrover.coms